MentorMob and the reinvention of learning - Greenstein, Shane M.; Polhans, Josh; Sabatte, Micheline ([London] : SAGE, 2016)
MentorMob had sprung from the passions of the company's co-founders, Kris Chinosorn and Vince Leung. By enabling participants to learn - and to crowdsource from each other while learning - the MentorMob site sought to both engage users at different stages of learning and to develop a compelling experience unobtainable without a crowd. Chinosorn and Leung needed to prioritize in order to achieve the growth and scale needed to become the world's utility for learning. What should they do next to keep MentorMob's growth on track?
Originally Published in: Greenstein, S., Polhans, J., & Sabatte, M. (2011). MentorMob and the Reinvention of Learning. 5-311-503. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; MentorMob (Firm); Entrepreneurship -- Case studies; Strategic planning -- Case studies; Business planning -- Case studies